Pre-existing adipose tissue signaling profile related to obesity determines disease outcome of COVID-19: addressing obesity should be a priority for future pandemic preparedness - Parker, Arifa; Petersen-Ross, Kelly; Maponga, Tongai; Parkar, Samina; Ahmed, Nadiya; Snyders, Candice I.; Kidd, Martin; Taljaard, Jantjie J.; Meintjes, Graeme; Koegelenberg, Coenraad F. N.; Kleynhans, Léanie; Smith, Carine (Frontiers in Endocrinology, 2025)
ObjectivesObesity is associated with COVID-19 severity and mortality. We investigated relationships between adipokines, cytokines and redox parameters with obesity, human immunodeficiency virus (HIV), severity and outcome.MethodsIn the exploratory study, adipose tissue (AT) was sampled in patients with COVID-19 on admission. Concentrations of leptin, adiponectin, resistin, interleukin 1 beta (IL-1b), IL-2, IL-6, IL-10, IL-17, tumor necrosis factor alpha (TNF-a), monocyte chemoattractant protein 1 (MCP-1), Trolox equivalent antioxidant capacity (TEAC), oxidative stress (H202) and malonaldehyde (MDA) were determined.ResultsThirty-eight biopsies of subcutaneous adipose tissue were obtained (prevalence of HIV was 39% and of obesity 61%). Higher IL-6 serum concentrations (p=0.03) were associated with more severe COVID-19, and higher serum IL-10 concentrations, (p=0.03) with mortality. People with obesity had higher leptin concentrations (p=0.03, and p<0.01), lower adiponectin/leptin (p=0.03 and p<0.01), and higher leptin/resistin ratios (p=0.09 and p<0.01) in both AT and serum respectively. Higher leptin/resistin (p=0.04) and lower adiponectin/resistin (p=0.05) ratios in AT, but not serum, were predictive of mortality. HIV was not associated with any differences. Relationships between resistin and redox indicators, TEAC and MDA, suggest a dysregulation of metabolic vs immune-relevant effect of resistin, which differentially predicted severity and mortality. SARS-CoV-2 RNA was detected in the subcutaneous AT in 3/8 patients who demised, but only in 1/30 who survived.ConclusionGiven the significant link demonstrated between leptin dysregulation in obesity and mortal severity of COVID-19, addressing obesity should be a priority therapeutic target in terms of future pandemic preparedness. Mechanistic studies are recommended to further elucidate the importance of metabolic vs immune modulation by resistin in COVID-19, to identify future therapeutic targets.